Tarjumān Al-Mustafīd: Answering the Need for Accessible Qur'anic Interpretation for The Masses - Chafid Wahyudi; Ika Khusnia Anggraini (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This article examines the interpretation model of Tarjumān al-Mustafīd as a means to address the need for Qur'anic interpretation for the general public. Using a qualitative method with content analysis and a systematic literature review, the study explores the approach used by Abd al-Raūf al-Fanṣūrī in his interpretation of the Qur'an. The results of the study indicate that al-Fanṣūrī's interpretation model includes three key elements: avoiding interpretations based solely on word meanings, providing context through asbāb al-nuzūl, narration isrāīlīyāt, historical accounts, and faidah letter explanations, and reconciling meanings to avoid controversial interpretations in both law and belief. The study concludes that Tarjumān al-Mustafīd is not a translation of classical interpretations, but rather a reproduction of al-Fanṣūrī's interpretation, referencing classical Arabic sources, and should not be referred to as a translation of Arabic interpretation into Malay. Overall, the interpretation model of Tarjumān al-Mustafīd provides a solution for addressing the need for Qur'anic interpretation for the general public and is a valuable contribution to the field of Qur'anic interpretation.